A comprehensive investigation on cellulose nanocrystals with different crystal structures from cotton via an efficient route. (15th January 2022) - Huang, Chengling; Yu, Houyong; Abdalkarim, Somia Yassin Hussain; Li, Yingzhan; Chen, Xiang; Yang, Xiaogang; Zhou, Ying; Zhang, Lianyang
Abstract: The crystal structures of cellulose nanomaterials play an important role in their morphologies and applications, however, there was still lacking systematic research on preparing various crystalline allomorphs of cellulose nanocrystals with high thermal stability. Herein, the efficient synthesis route was presented to design various crystalline allomorphs of cellulose from cotton. And then, cellulose nanocrystals with different crystal structures (CNC-I, CNC-II, CNC-IIIII, CNC-IVII ) were prepared by hydrogen peroxide hydrolysis of resultant cellulose. Overall, needle-like CNC-I (length of 180 ± 25 nm, diameter of 12 ± 2 nm), near-spherical CNC-II (diameter of 101 ± 12 nm), and spherical CNC-IIIII (diameter of 22 ± 3 nm) and CNC-IVII (diameter of 21 ± 2 nm) all exhibited remarkable dispersibility and thermal stability ( T max > 357 °C). This work provides a simple and low-cost synthesis route for various crystalline allomorphs of CNCs with high thermal stability from the same raw materials (cotton).